RESPONSE OF TOMATO GROWTH TO FOLIAR AND SOIL APPLIED NITROGEN ALONE OR WITH POTASSIUM AND PHOSPORUS. 2) NUTRIENTS CONCENTRATION - Abdulkareem, M.A.; Ansari, A.; Mehdi, S.A. (Emirates Journal of Food and Agriculture, 1997)
Please see the scanned pdf version in full text